ANALISIS BIODIVERSITAS JENIS-JENIS TUMBUHAN LIANA DI TAMAN NASIONAL BATANG GADIS RESORT 7 SOPOTINJAK KABUPATEN MANDAILING NATAL SUMATERA UTARA - ainun mardia siregar; Husnarika Febriani; Melfa Aisyah Hutasuhut (Program Studi Biologi Fakultas Sains dan Teknologi Universitas Islam Negeri Sumatera Utara, 2021)
Climbing plants or what is known as Liana is a type of plant that is characteristic of tropical rainforest ecosystems. This study aims to determine the types of lianas, diversity index and wealth index, the method used is descriptive survey method with the sampling technique using the quadratic method, the number of plots used is 24 plots in three transects. Found 12 families consisting of 27 species of lianas with a total number of 1082 individuals. The family with the most species is the Araceae family with 5 species, the families with the least species are Dioscoreaceae, Polypodiaceae, Rosaceae, and Vitaceae, each of which has only one species, the species with the highest number of individuals ishighest number of individuals. Ficus villosa Blume with a total of 182 and species with thethe least amount is Alstonia sp, namely 14 individuals. The species with the highest Importance Value Index (IVI) was Entada spiralis Ridl with a value of 54.84. Liana Diversity Index in Batang Gadis Resort 7 National Park is H '3.14 which is included in the high diversity category, one of the factors that resulted in the high diversity value of lianas in BGNP is the availability of many trees as host plants for habitus liana, while the wealth index value of lianas in Batang Gadis Resort 7 National Park is 3.47 which is included in the medium wealth category, one of the factors causing the wealth index value to be included in the moderate category is the number of species found as many as 27 species.